Orchestration to improve the performance and sustainability of family companies - Sri Gunawan; Sugiarto Koentjoro (Cogent Business & Management, 2023)
The purpose of this study is to identify the efforts made by family businesses to develop knowledge resources in order to improve innovative performance and market adaptability. This study employs a single case study exploratory design, with "indepth interviews" conducted with 9 participants from three companies in one group in Indonesia. The findings revealed a process of developing human and social capital resources to expand the company's knowledge resources. Other findings identified the critical processes of empowerment and authority coordination. It was used to establish a family business that encourages generational involvement and is capable of supporting the process of increasing knowledge resources. It was used to establish a family business that encourages generational involvement and is capable of supporting the process of increasing knowledge resources. Furthermore, this research can be a foundation for encouraging resource orchestration in family businesses to increase sustainability. It is one of the studies that integrate resource orchestration theory with management knowledge and explains the importance of creating a conducive family business for sustainability due to generational involvement.
Keywords: 650; corporate strategy; corporate sustainability; Family company; managing conflict; managing knowledge; resource orchestration